2015
DOI: 10.18632/oncotarget.6340
|View full text |Cite
|
Sign up to set email alerts
|

Genomic binding and regulation of gene expression by the thyroid carcinoma-associated PAX8-PPARG fusion protein

Abstract: A chromosomal translocation results in production of an oncogenic PAX8-PPARG fusion protein (PPFP) in thyroid carcinomas. PAX8 is a thyroid transcription factor, and PPARG is a transcription factor that plays important roles in adipocytes and macrophages. PPFP retains the DNA binding domains of both proteins; however, the genomic binding sites of PPFP have not been identified, and only limited data exist to characterize gene expression in PPFP thyroid carcinomas. Therefore, the oncogenic function of PPFP is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
2
19
0
4
Order By: Relevance
“…However, the results of this mouse thyroid gland ChIP-seq are highly concordant with a ChIP-seq dataset that we previously published on PPFP stably expressed in the PCCL3 rat thyroid cell line [11], which supports the validity of both models. For example, both ChIP-seq studies showed enrichment of PPFP peaks within 1 kb of TSS’s, and both showed that most peaks contain a PAX8 motif and/or a PPARG motif near the peak center, indicating that both DBDs within PPFP are functional.…”
Section: Discussionsupporting
confidence: 88%
“…However, the results of this mouse thyroid gland ChIP-seq are highly concordant with a ChIP-seq dataset that we previously published on PPFP stably expressed in the PCCL3 rat thyroid cell line [11], which supports the validity of both models. For example, both ChIP-seq studies showed enrichment of PPFP peaks within 1 kb of TSS’s, and both showed that most peaks contain a PAX8 motif and/or a PPARG motif near the peak center, indicating that both DBDs within PPFP are functional.…”
Section: Discussionsupporting
confidence: 88%
“…As these drugs are already in clinical or preclinical use, expedient translation to the clinic is possible. The findings presented in this study may also have broader significance beyond GCT, specifically for malignancies that coexpress these proteins such as epithelial ovarian cancer (48,49), colorectal cancer (50), and thyroid cancer (51,52).…”
Section: Discussionmentioning
confidence: 79%
“…However, the mechanisms involved in tumorigenesis and progression remains unclear. Unlike other driver mutations in thyroid cancers that overexpress kinase signaling pathways, PAX8-PPARG gene fusion involves tumor immunology and several cancer-related pathways such as apoptosis, cell cycle, and motility [82].…”
Section: Follicular Thyroid Cancer (Ftc)mentioning
confidence: 99%